From Defensor civitatis to Ombudsman - Andrea Trisciuoglio (Journal of Interdisciplinary History of Ideas)
This special issue of the Journal of Interdisciplinary History of Ideas contains papers from two workshops held in Zaragoza and Turin as part of the project “Citizenship, Participation, Representation”, funded by the University of Turin. For both meetings, it was decided to focus on the Ombudsman. This figure is at the heart of current forms of informal participation and representation.